The principal's strategy in developing pedagogical professionalism of kindergarten teachers: a case study at tkit al-qur'an at-tartil, sukabumi city - Susi Widiyawatia; R. Supyan Sauri; Abdul Holik (At Turots: Jurnal Pendidikan Islam, 2025)
Early childhood education is the initial stage for developing the potential of children, who have unique characters. It requires treatment and educational strategies that suit their needs. Principals as leaders of early childhood education institutions need to ensure that teachers can carry out their duties professionally and are able to develop children's potential in all aspects of their development. The reality in the field shows that there are still various challenges in organizing kindergarten education, especially those related to the quality of the learning process. One important aspect that affects the quality of learning in kindergarten is the competence and professionalism of teachers. Faced with this fact, school principals can implement various strategies to develop teachers' pedagogical professionalism. Strategies to improve teachers' pedagogical competence must be integrated and sustainable. The purpose of this study is to analyze and describe the principal's strategy in developing kindergarten teachers' pedagogical professionalism. This research used a qualitative approach with a case study method. The research subjects were principals and teachers of TKIT Al-Qur'an At-Tartil in Sukabumi City. The results illustrate that principals make strategic efforts in developing teachers' pedagogical professionalism, starting from understanding the characteristics of students, mastering learning theories and principles, curriculum development, learning design, to implementing educational and dialogical learning. Principals carry out several strategies in developing teachers' pedagogical professionalism, including understanding the characteristics of learners, including physical, cognitive, social-emotional, moral, and spiritual aspects of early childhood, strengthening teachers' understanding of learning theories and principles in accordance with the characteristics of early childhood, as well as utilizing ICT, facilitating teachers in designing effective and enjoyable learning, starting from formulating goals, choosing strategies, methods, media, and learning resources that are in accordance with the characteristics of children.